КОМПЕТЕНТЛИ ЁНДАШУВ АСОСИДА БЎЛАЖАК ЎҚИТУВЧИЛАРНИНГ МУСТАҚИЛ ФАОЛИЯТИНИ ТАШКИЛ ҚИЛИШНИНГ ПЕДАГОГИК ТЕХНОЛОГИЯЛАРИ - Адинаев, Ш.Ш. (SCIENCE and SOCIETY, 2018)
The article deals with the interpretation of the essence of the concept «technology», the organization of independent work of students, the components necessary for designing the technology of independent work in the context of implementing the competence approach are revealed.